Women and Gender in International Relations: in addition to “everyday prisons” and epistemological - PASSOS, Rodrigo Duarte Fernandes dos (Faculdade de Filosofia e Ciências, 2017)
How is it possible to deal with women and gender in a highly masculinized disciplinary field and monopolized by Political Science - International Relations -, which is associated with “everyday prisons” such as to the gender-related distinction between public and private spheres, and war and peace? This is the question that summarizes the focus of this text. The hypothesis provided to answer this problem summarily states that the gender approach in this field is guided by the parameters and limits of Political Science. Alternatively, an interrelational perspective coherent with the gender approaches can be obtained in holistic terms, of totality with the approach of the uneven and combined development, in terms of the coexistence of multiple societies, interactions, relations and causalities, without the specific emphasis of Political Science that permeates directly and indirectly almost the whole International Relations approach. Submissão: 2017-05-11 Aceite: 2017-08-13